2006
DOI: 10.1111/j.1475-3588.2006.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Child Mental Health is Everybody's Business: The Prevalence of Contact with Public Sector Services by Type of Disorder Among British School Children in a Three‐Year Period

Abstract: Method: A third of the children from the 1999 British Child and Adolescent Mental Health Survey were followed-up over 3 years. Parents provided summary information on service contacts in relation to mental health; selected subgroups provided more detailed information by telephone interview. Results: Common overlaps in service use were between health services, between teachers and educational specialists, and between the latter and CAMHS or social services. Services other than primary health care saw more child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
120
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 44 publications
8
120
0
Order By: Relevance
“…A previous study found significantly higher lifetime rates of utilization of social and educational services in conduct disorders compared to other mental health disorders as a whole [30]. A longitudinal study on service contacts on a nationally representative sample found that children with CD were more likely to be in contact with social services, teachers and special educational needs agencies than children with other disorders [7].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found significantly higher lifetime rates of utilization of social and educational services in conduct disorders compared to other mental health disorders as a whole [30]. A longitudinal study on service contacts on a nationally representative sample found that children with CD were more likely to be in contact with social services, teachers and special educational needs agencies than children with other disorders [7].…”
Section: Introductionmentioning
confidence: 99%
“…The present study explores these associations, with a focus on children with emotional disorders, which are associated with poorer access to care (Ford, Hamilton, Meltzer, & Goodman, 2007). Only one in four children with a diagnosable mental health problem accesses treatment and this is lowest for children with internalizing disorders, including anxiety and depression, rather than externalizing disorders (Ford et al, 2007). Focusing on a single problem type when investigating care pathways also facilitates the interpretation of results, as they are less likely to be affected by differences in prevalence of mental health problems across ethnic groups, which is not well understood (Green, 2005).…”
mentioning
confidence: 99%
“…There is little current evidence about differences in mental health service access and discharge in England for children and young people with different ethnic backgrounds. The present study explores these associations, with a focus on children with emotional disorders, which are associated with poorer access to care (Ford, Hamilton, Meltzer, & Goodman, 2007). Only one in four children with a diagnosable mental health problem accesses treatment and this is lowest for children with internalizing disorders, including anxiety and depression, rather than externalizing disorders (Ford et al, 2007).…”
mentioning
confidence: 99%
“…If the broad confidence interval was ignored and the prevalence was directly translated into clinic budgets, this discrepancy could clearly lead to disastrous under-provision for children with hyperkinesis. However, previous studies have repeatedly shown that most children with psychiatric disorders do not receive any specialist help [21] Thus, even a substantial underestimate of prevalence leaves the main message unchanged, namely that the need for services outruns provision. In some circumstances, indicative rather than exact prevalence findings may be sufficiently accurate.…”
Section: Overall Discussionmentioning
confidence: 96%